Distinct Clinical and Experimental Characteristics in the Patients Younger than 60 Years Old with Myelodysplastic Syndromes - Li, Xiao (Public Library of Science, 2013)
Myelodysplastic syndromes (MDS) mainly occur in elderly individuals in Western countries. However, MDS is commonly found in young individuals (<60 years) in Asia. The reason for the high incidence in younger individuals is still unclear, and the differences in disease features between young and elderly patients with MDS have been not well recognized. To explore these issues, in this study, we analyzed the clinical and experimental characteristics of MDS in the patients younger and older than 60 years old and characterized the potential age-associated differences. The results showed that over half of the patients with MDS (61.9%) were younger than 60 years old upon the first diagnosis. The younger patients were more likely to be female, who have lower risk and less advanced MDS. The occurrence of trisomy 8 and bone marrow failure were more frequent in the younger patients than the older ones. The marrow CD34+ cells in the younger patients showed lower proliferation and higher apoptosis in comparison with that in the older ones. Obvious amplification of T cells and low CFU formation could be found in the younger patients. CFU formation was significantly increased in the younger patients after the removal of activated T cells. In addition, the younger patients had a lower frequency of p15INK4B methylation, longer survival expectancy and less AML transformation. In summary, the younger patients with MDS in China may show more benign disease features than the older ones. Enhanced immunological response may be involved in the pathogenesis of MDS in the patients younger than 60 years.